2013
DOI: 10.1177/1076029613488936
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII in the Setting of Acute Ischemic Stroke Among Patients With Suspected Hypercoagulable State

Abstract: Background Elevation of factor VIII is associated with higher risk of large vessel arterial occlusions including stroke. Methods Factor VIII levels were examined in consecutive patients with acute ischemic stroke (AIS) presenting to a single center between July 2008 and May 2012. Factor VIII levels exceeding the laboratory reference range were considered elevated (>150%). Results Factor VIII level was elevated in 72.4% (84 of 116) of the patients. Elevated factor VIII level was more frequent in blacks, dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 22 publications
(34 reference statements)
1
31
0
5
Order By: Relevance
“…10 However, we found that combined elevations of FVIII and vWF were associated with worse neurologic outcome (defined as discharge modified Rankin Scale score > 2). 28 There also appeared to be a clinically significant association between FVIII and vWF levels and inpatient complications (such as infection), neurologic deterioration (defined as an increase in NIHSS score of 2 or more within a 24-hour period 37 ), and recurrent thrombotic events following acute ischemic stroke.…”
Section: Factor VIII and Strokementioning
confidence: 70%
“…10 However, we found that combined elevations of FVIII and vWF were associated with worse neurologic outcome (defined as discharge modified Rankin Scale score > 2). 28 There also appeared to be a clinically significant association between FVIII and vWF levels and inpatient complications (such as infection), neurologic deterioration (defined as an increase in NIHSS score of 2 or more within a 24-hour period 37 ), and recurrent thrombotic events following acute ischemic stroke.…”
Section: Factor VIII and Strokementioning
confidence: 70%
“…1,13 This study proposes a novel model by which clinicians can use patients’ baseline characteristics to predict which patients will have persistent elevation of FVIII post-AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has illustrated an association between FVIII elevation and increased risk of venous thrombosis and recurrent thromboembolic events. 14 Additionally, elevated FVIII is an independent risk factor for acute ischemic stroke (AIS) and coronary artery disease. 1,5,6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Patients who have acute ischemic cerebrovascular disease(AICVD) complicating coronary heart disease(CHD) are frequently encountered in clinical practice 5 , and tend to have worse outcomes such as the loss of the independent walking even independent living. 6 Due to the medical technology advancements in the last 10 years, our understanding of the pathophysiology of stroke is expanding, This has led to the development of numerous theories such as intimal injury, 7, 8 activation of coagulation system, 9,10 and inflammatory immune regulation, 11,12 etc. However, all treatments on stroke were aimed to improve neurological deficit and its prevention, systemic observations, and studies of the correlations of neurological deficits, and hematological indices of these patients are of great value for the choice of the therapy and the improvement of the prognosis.…”
Section: Introductionmentioning
confidence: 99%